2012
DOI: 10.1590/s0104-11692012000400013
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of auriculotherapy for the reduction of stress in nursing students: a randomized clinical trial

Abstract: This study is a randomized single-blind trial, which aimed to evaluate the efficacy of true auriculotherapy and placebo auriculotherapy in reducing the stress levels of mid-level Nursing students of the School of Nursing of the Beneficência Portuguesa Hospital. Seventyone students with average, high and very high scores, according to Vasconcellos' List of Stress Symptoms, were divided into three groups: Control (25), Auriculotherapy (24), and Placebo/Sham (22). They were evaluated at the baseline, 8th and 12th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 11 publications
1
13
0
4
Order By: Relevance
“…In summary, the focus of this research was stress among nursing students, based on the understanding that this type of study contributes to the planning of strategies for mental health promotion in student daily life. Previous studies pointed out effective strategies to minimize stress and improve the well-being of students, such as Mindfulness (15)(16) , the biofeedback method (17) , and auriculotherapy (18) . However, this study advanced in the sense of making explicit that the coping resources such as social support have different effects on each type of stressor and that this should be considered in the planning of actions to promote mental health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, the focus of this research was stress among nursing students, based on the understanding that this type of study contributes to the planning of strategies for mental health promotion in student daily life. Previous studies pointed out effective strategies to minimize stress and improve the well-being of students, such as Mindfulness (15)(16) , the biofeedback method (17) , and auriculotherapy (18) . However, this study advanced in the sense of making explicit that the coping resources such as social support have different effects on each type of stressor and that this should be considered in the planning of actions to promote mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the knowledge produced concerning stress among nursing students, two study perspectives were identified in the literature: the first refers to the investigation of potentially stressor factors/elements in daily life and the implications for the mental health of these subjects (4)(5)(6)(7)(8)(9) , while the second branch composes the coping strategies for maintaining the well-being in the university context (10)(11)(12)(13)(14)(15)(16)(17)(18) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] In our case, a massive impairment in physical status occurred at a period of her life when physical health is naturally assumed and important in the context of the physical and emotional changes of adolescence. This can generate profound mental, emotional and physical stress.…”
Section: Well-being Self-assessmentmentioning
confidence: 76%
“…Estes fatores estressores podem ocasionar desordens psicológicas e físicas (fadiga, ansiedade e cansaço), afetando a vida acadêmica e em consequência o futuro profissional, pois há comprometimento do cotidiano do aluno. Sendo as alterações de saúde: depressão, ansiedade, estresse, aumento do sentimento raiva, angústia, desespero, mau humor, má qualidade do sono, uso de álcool, cansaço e fadiga (11)(12)(13)(14)16,(18)(19)(20)26,28,(29)(30)(31)(32)(33) , descritas como transitórias e de fácil superação pelos estudantes investigados.…”
Section: Resultsunclassified